Capturing the circadian rhythms of free-running blind people with 0.5 mg melatonin - Lewy, Alfred J; Bauer, Vance K; Hasler, Brant P; Kendall, Adam R; Pires, M.Laura N; Sack, Robert L (Brain research, 2001)
We have recently shown that six of seven totally blind people (who had free-running circadian rhythms with periods longer than 24 h) could be entrained (synchronized) to a nightly dose of 10 mg melatonin. After treatment discontinuation and re-entrainment to the 10 mg dose, we further found in three of these subjects that the dose could be gradually reduced to 0.5 mg without loss of effect. The question then arose: can a de novo (starting) dose of 0.5 mg initially capture free-running rhythms? Following withdrawal of the stepped-down 0.5 mg dose and consequent release into a free-run, the same three individuals were given 0.5 mg of melatonin de novo. All entrained within a few weeks.